Maternal mortality in the National Edgardo Rebagliati Martins IPSS Hospital 1958-1991. - Pacheco, José (2015)
The review of 176 maternal deaths in the National Hospital Edgardo Rebagliati Martins (HNERM) of the Peruvian Institute of Social Security (LPSs) between 1958 and 1991 indicates that 71% were due to direct obstetric death, including 24% by infections 22% induced hypertension and 16% Bleeding-, was 16% indirect and 13% nonobstetric. The maternal mortality rate in the 33 years was 39 per 100 000 births Although the rate is relatively acceptable, deaths were mostly from preventable causes, requiring for you diminish a clearly defined institutional policy, care and management levels well implemented uniformly institutional protocols and manuals.